2021
DOI: 10.1111/eci.13680
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulphide in liver glucose/lipid metabolism and non‐alcoholic fatty liver disease

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 101 publications
1
3
0
Order By: Relevance
“…Thereby by, a significant improvement has been observed regarding albumin, ammonia, ALP, AST, ALT, HR, troponin I, LDH, and CK-MB serum levels following their administration with a more relevant improvement has been observed following NaHS administration when compared with the control group (I). In line with our observed results, (Ertugrul et al 2021 ; Guo et al 2020 ; Yang et al 2021 ; Sun et al 2021 ; Mateus and Prip-Buus 2022 ) proved the efficiency of the administration of exogenous hydrogen sulphide donor and MSCs in alleviating cardiac and liver dysfunctions by promoting tissue regeneration, inhibiting fibrosis, and regulating immune responses.…”
Section: Discussionsupporting
confidence: 89%
“…Thereby by, a significant improvement has been observed regarding albumin, ammonia, ALP, AST, ALT, HR, troponin I, LDH, and CK-MB serum levels following their administration with a more relevant improvement has been observed following NaHS administration when compared with the control group (I). In line with our observed results, (Ertugrul et al 2021 ; Guo et al 2020 ; Yang et al 2021 ; Sun et al 2021 ; Mateus and Prip-Buus 2022 ) proved the efficiency of the administration of exogenous hydrogen sulphide donor and MSCs in alleviating cardiac and liver dysfunctions by promoting tissue regeneration, inhibiting fibrosis, and regulating immune responses.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, it was shown that this model of simple fatty liver in female rats also presented reduced hepatic H 2 S production, with BemA treatment restoring the biosynthesis of this gasotransmitter [36 & ]. Other in-vivo and in-vitro models of NAFLD show impaired hepatic H 2 S synthesis, with H 2 S donor treatment being effective in reducing hepatic steatosis and NASHrelated features [37]. Therefore, the increase in H 2 S production caused by BemA treatment may be an additional mechanism contributing to ameliorate hepatic steatosis [36 & ].…”
Section: Bempedoic Acid and Nafld: Results In Animal Models And Propo...mentioning
confidence: 99%
“…In the presented work, we show that the administration of BemA to female Sprague-Dawley rats fed an HFD supplemented with a 10% w/v fructose solution as a beverage (HFHFr diet) reverses the decreased production of liver H 2 S induced by consumption of the HFHFr diet. As H 2 S has a prominent role in the regulation of liver glucose and triglyceride metabolism [22], the recovery of liver H 2 S production induced by BemA could contribute to the recently described therapeutic effect of BemA in several experimental models of NAFLD [18,23].…”
Section: Discussionmentioning
confidence: 99%